Existential waste in a sample University professors and students (Journal of the College of Basic Education, 2022)
There is an issue that transcends freedom and democracy in its usual propositions. We are in the process of a precondition for them represented in the recognition of human humanity, his being, his inviolability, his immunity and his unconditional primary value. From this point of view, the problem of the current study is determined by the following question: Is there at the current national level recognition of the human being as a value and an entity and what they impose a priori in terms of sanctity, immunity and rights?